2014
DOI: 10.1016/j.neuroscience.2014.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal ketamine exposure causes impairment of long-term synaptic plasticity in the anterior cingulate cortex of rats

Abstract: Ketamine, a dissociative anesthetic most commonly used in many pediatric procedures, has been reported in many animal studies to cause widespread neuroapoptosis in the neonatal brain after exposure in high doses and/or for prolonged period. This neurodegenerative change occurs most severely in the forebrain including the anterior cingulated cortex (ACC) that is an important brain structure for mediating a variety of cognitive functions. However, it is still unknown whether such apoptotic neurodegeneration earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Ketamine hydrochloride, known simply as ketamine, a non-competitive N- methyl- D -aspartate receptor (NMDAR) antagonist, is commonly used as a pediatric anesthetic. However, multiple animal studies have conclusively shown that prolonged neonatal exposure to ketamine, or its congener, caused widespread neuroapoptosis that ultimately manifested in deficits of learning and memory and impairments in long-term synaptic plasticity in adulthood (Huang, Liu, Jin, Ji, & Dong, 2012; Jevtovic-Todorovic et al, 2003; Wang et al, 2014; Womack et al, 2013). A compensatory upregulation of the NMDARs develops significantly when ketamine is withdrawn, which triggers neuronal excitotoxicity leading to neuroapoptosis (Kokane & Lin, 2016; Slikker et al, 2007; Zou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine hydrochloride, known simply as ketamine, a non-competitive N- methyl- D -aspartate receptor (NMDAR) antagonist, is commonly used as a pediatric anesthetic. However, multiple animal studies have conclusively shown that prolonged neonatal exposure to ketamine, or its congener, caused widespread neuroapoptosis that ultimately manifested in deficits of learning and memory and impairments in long-term synaptic plasticity in adulthood (Huang, Liu, Jin, Ji, & Dong, 2012; Jevtovic-Todorovic et al, 2003; Wang et al, 2014; Womack et al, 2013). A compensatory upregulation of the NMDARs develops significantly when ketamine is withdrawn, which triggers neuronal excitotoxicity leading to neuroapoptosis (Kokane & Lin, 2016; Slikker et al, 2007; Zou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One study showed evidence of neurotoxicity of sevoflurane at an earlier stage—PD6—associated with caspase activation, apoptosis, and increased levels of beta‐amyloid proteins , and a similar study showed that neonatal ketamine results in long‐term effects .…”
Section: Resultsmentioning
confidence: 99%
“…Spike discharge was recorded at the current clamp mode and postsynaptic currents were recorded at the voltage-clamp mode. Detailed methodology has been described in our previous reports (Gong et al, 2010 ; Wang et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Bicuculline (10 μM), CNQX (10 μM), D-APV (50 μM) and TTX (1 μM) were dissolved in the ACSF to their final concentration on the day of the experiment and applied to the brain slices with perfusion when tested. Selectivity and target concentrations were chosen based on preliminary experiments and previous reports (Gong et al, 2010 ; Wang et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%